Analysis of the effectiveness of the training program for fire commanders in leadership and command at fire interventions - Varga, Tihomir (Crisis Management Days, 2025)
The Training Program for Fire Commanders in Leadership and Command at Fire Interventions (VIZ) has been implemented in the fire service system of the Republic of Croatia since 2018. The program consists of four levels, depending on the size of the force formation at the intervention. So far, 26 groups have completed the VIZ-I level, 10 groups VIZ-II level, and one group VIZ-III level for different sizes of formations at fire interventions. The groups consist of professional and volunteer fire department members, with the basic requirement of successfully passing the exam for firefighters with special authorities and responsibilities. Before introduction the VIZ Program, there was no systematic training for fire intervention commanders; instead, partial solutions were implemented through various specialized firefighter training programs. The additional challenge is applying VIZ Program elements in the regular practice of fire departments, which includes integrating new procedures and tools into existing systems and overcoming resistance to change. By analysing the impact of the VIZ Program on leadership and command at fire interventions, this study aims to highlight the importance of training intervention commanders and to identify positive experiences and areas for further development of this program. The research included an analysis of the program content, combining theoretical instruction and practical exercises, to adopt specific procedures and leadership mechanisms, comparing the program content with the application of these elements in practice during interventions through a review of characteristic fire intervention reports. At the end of each training, participants were asked several questions about the implementation and application of the VIZ Program through a group interview method. Responses were given orally before the entire group of participants, and summaries were recorded by the program leader. Conclusions about the program's effectiveness were drawn from the collected and analysed data. The results showed a high success rate of participants and significant improvements in leadership and command skills, especially in decision-making processes, communication, and team coordination. The training program resulted in positive reactions from participants, indicating its potential to develop leadership and command skills. This contributed to the comprehensive development of fire commanders' competencies. Implementing this program could significantly strengthen the overall operation of the firefighting system, although there are certain challenges related to the legal framework, implementation, and application in daily practice. The research emphasizes the importance of a systematic approach to training fire commanders and the need for continuous implementation and evaluation of the program. It also highlights the opportunity for further development and improvement of training methods.